Prevalence and Molecular Characterization of Metallo β-Lactamase Producing Gram-Negative Pathogens Causing Eye Infections - Rameshkumar, Gunasekaran; Dhandapani, Ranjithkumar; Lalitha, Prajna; Rajapandian, Siva Ganesa Karthikeyan; Palanivel, Velmurugan; Thangavelu, Sathiamoorthi; Alyousef, Abdullah A.; Albalawi, Thamer; Alam, Pravej; Zubair, Mohammad; Saleh, Fayez M.; Alatawi, Fuad Abdullah; et al. (Frontiers in Public Health, 2022)
Purpose: Metallo β-lactamases (MβL) production is a worldwide problem, particularly in gram-negative bacteria. As scanty data is available on the prevalence of MBL, the present study is being undertaken to determine the prevalence, antibacterial sensitivity patterns, and molecular characterization of MβL associated resistant genes in gram-negative bacteria isolated from ocular infections. Material and Methods At a tertiary eye care center in south India, 359 gram-negative pathogens, 200 isolates from eye infections, and 159 isolates from normal flora of the eye were studied. A gold standard microbiology method was used to identify the isolates. An antibiotic double disc synergy test and a combination disc test were used to detect MβL production. Multiplex PCR was used to investigate the molecular characteristics of the MβL encoding genes blaVIM, blaIMP, and blaNDM. Results Of the 359 gram-negative bacterial pathogens, Pseudomonas aeruginosa 108 (30.1%) and Enterobacter agglomerans 46 (12.8%) were commonly isolated. High prevalence of P. aeruginosa 81% (17 strains) was detected as an MβL producer and it shows 100% resistance to 2nd and 3rd generation cephalosporins and meropenem. Multiplex PCR detected only the blaVIM gene in 56 (28%) of various eye infections and 27 (17%) of normal flora of the gram-negative bacteria (GNB). The blaVIM gene is detected predominantly in 51.8% of keratitis and 21.4% of postoperative endophthalmitis. High prevalence of the gene was detected in P. aeruginosa 42.9% (24 of 56) and Alcaligens denitrificans 10.7% (6 of 56) from eye infections. Whereas, in the control group, P. aeruginosa and E. coli each had 14.8% (4 of 27) that were shown positive. Conclusion The emerging MβLs mediated resistance among P. aeruginosa is a challenging task for ophthalmologists, especially in patients with endophthalmitis and bacterial keratitis. This local knowledge will aid in advising appropriate antibiotic use and avoiding unnecessary antibiotic prescriptions, which are highly warranted.